The Influence of Intelligence on Student Learning Achievement Seen from Learning Styles (Case Study on Math, Science, and English Lessons - Budiman, Budiman; Susongko, Purwo; Nugraha, Rahmad Agung (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the effect of intelligence on learning achievement in Mathematics, Science, and English based on students’ learning styles. Using a quantitative approach, the research ensures statistical significance and minimizes researcher subjectivity while analyzing a large sample. The findings reveal that intelligence significantly influences academic performance across subjects, with varying contributions depending on learning styles. Visual learners show the highest intelligence-based contribution to Mathematics achievement (9.10%), followed by Science (8.20%) and English (5.10%). Auditory learners demonstrate a high contribution to Mathematics (7.40%), English (4.30%), and Science (4.10%). In contrast, kinesthetic learners exhibit the lowest contribution, with 0.70% for Mathematics, 0.50% for Science, and 0.30% for English. These results indicate that learning styles moderate the relationship between intelligence and academic success, with visual learners benefiting the most, particularly in Mathematics and Science, which require abstract understanding. The lower intelligence contribution for kinesthetic learners suggests that interactive, practice-based teaching methods are necessary to enhance their learning outcomes. The study underscores the importance of aligning instructional strategies with students’ learning styles to optimize academic achievement. A visual-based approach proves more effective in subjects requiring conceptual understanding, while kinesthetic learners may need more hands-on, experiential learning methods to improve their performance.